Analysis of heart rate variability as identifier of signs of occupational stress: cross-sectional descriptive observational study - Palmeira de Oliveira Bittencourt, Jouse Marri; Pereira de Lima, Luara Lee; Tavares, Nathália Julie; da Silva, Rodrigo Marcel Valentim (Manual Therapy, Posturology & Rehabilitation Journal, 2022)
Background: There is great concern in the world about worker stress and quality of life, since a significant number of companies show that physical and mental suffering are one of the main causes of absenteeism, generating high business costs due to low productivity. Stress at work ends up affecting not only the professional income but also your health. Objective: To investigate the correlation between stress level and heart rate variability (HRV). This is a cross-sectional observational survey of 20 workers from the administrative, maintenance and concierge sectors of a condominium management company. Cardiac biofeedback equipment (BFC) was used, which evaluates the activity of the Autonomic Nervous System (ANS), as well as the influence exerted by the limbic system (system of emotions). A LIPP questionnaire was level of cortisol. Results: It can be observed that there is a correlation between the coherence note (BFC) and the working time, a moderate correlation between the consistency score, coherence and evening cortisol, it is also observed that there is an association between the coherence state and the LIPP questionnaire. Conclusion: In general, there was an association between the numerical variables and the heart rate variability, but what was shown to be a greater association was the interaction of the questionnaire with the coherence state at the cortisol level.